Critical assessment of the human resource challenges and issues faced by hospitality and tourism sector: x - Javakhoshvili, Ivane; Shaburishvili, Shota; Shaburishvili, Shota; Khoshtaria, Tornike (Management and Administration Journal, 2021)
Hospitality and tourism are an industry which have become an essential revenue stream for many developing countries. Organizations and their management have to deal with many difficulties in recruiting, developing and maintaining well motivated employees, who must give high-quality service to demanding customers7. In this article all the difficulties and issues related to human resource management which exists in tourism and hospitality industry will be critically evaluated, particularly pertaining to organization management and personnel training and motivation. in order to form, develop and maintain effective and motivated personnel